Role of Microfinance in Eradication of Poverty in India – Perspectives & Operations - et. al., Dr. Shubhra Rahul, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In developing economies and particularly in rural areas, many activities that would be classified in the developed world as financial are non-monetized: that is, money is not used to carry them out. This is often the case when people need the services money can provide but do not have dispensable funds required for those services, forcing them to revert to other means of acquiring them. Often money is needed for the purposes; by a chunk of the population like lifecycle needs such as weddings, funerals, childbirth, education, home building, widowhood and old age, personal emergencies such as sickness, injury, unemployment, theft, harassment or disasters such as fires, floods, cyclones and man-made events like war or bulldozing of dwellings, investment opportunities: expanding a business, buying land or equipment, improving housing, securing a job (which often requires paying a large bribe). This paper is divided into two parts, perspectives and operations of Micro Finance. Perspectives portion deals theoretical conceptions and Operations portion deals with organizational insights and models plus some governmental compliances.